HUBUNGAN ANTARA KARAKTERISTIK AGROEKOLOGI PERKEBUNAN KARET (Hevea brassiliansis L) DENGAN HASIL KARET DI LAMPUNG - Andarias Makka Murni (Jurnal Ilmu Tanah dan Lingkungan, 2015)
The productivity of rubber (Hevea brassiliansis L) are determined by agro-ecological conditions in which the commodity is developed. Lampung province is one of the producers of the commodity. To determine the relationship between the characteristics of agroecology with rubber yield, the study of correlation of agroecological characteristics of the rubber yield was conducted in Lampung. The study was conducted at three locations, namely Tulang Bawang, Central Lampung and Way Kanan regency. The study used a survey method to collect rubber yield, as well as the character of agroecology including soil properties and climate data especially the rainfall based on the land evaluation guidelines for agricultural commodities. The results showed that the character of rubber plantations agroecology in Lampung belongs to a class of suitable (S2). Soil fertility of rubber plantation in all locations generally at the level of low to moderate, except for potential K in Way Kanan and Tulang Bawang is high and available P is high in all locations. Low soil pH and levels exchangeable Al at moderate to a high level in the depth of 20-40 cm soil surface potentially to fix P, therefore, making it unavailable to plants. There was a strong correlation between soil properties and yield of rubber in Tulang Bawang and Way Kanan, but in Central Lampung, the relationship is very weak. Recommended land quality improvement technology in rubber plantations through liming and the use of organic materials to eliminate/prevent fixation of P in the soil due to low soil pH and the levels of exchangeable Al at a medium and high level in the layer 20-40 cm below the soil surface. Keywords: Character agroecology, Hevea brassiliansis L, land suitability